Analisis Kandungan Timbal (Pb) dan Tingkat Pengetahuan Orang Tua dan Guru Tentang Timbal (Pb) Pada Mainan Edukatif Balita di Taman Kanak-Kanak (TK) Kecamatan Medan Denai Tahun 2014 - devi destika pohan; indra chahaya; evi naria (Lingkungan dan Kesehatan Kerja, 2014)
Consumer’s product has become daily needed. But most of the consumer’s product like educational toys has contaminated by heavy metals Pb. Pb in educational toys commonly from paints and the raw materials. Toys that contaminated by heavy metals Pb could be asorb by the body of kids by putting the toys to in their mouths. Parents and teachers take a big role to choose toys and monitoring children while they are playing around. The aim of this study is to identity a number of heavy metal Pb and the parents and teacher’s knowladge about heavy metal Pb in educational toys for children under five years old. This research will be held in kindergarten at Kecamatan Medan Denai. This study is a descriptive which the parents population and sample is about 30 people taken by total sampling technique. Population of teachers is about 37 people with total samples is 30 people got by the simple random sampling technique. Data will be analyzed descriptively in tables and narration. The study found that (75%) of educational toys for children under five years old consisting 1,48-8,05 ppm of Pb. It means Pb is still under value limit. Parent’s knowladge about Pb in educational toys for chldren under five years old is in intermediate level about (33,3%) and in good level about (66,7%). Teacher’s knowladge about Pb in educational toys is inintermediate level of knowladge, that is about (6,7%) and in good level about (93,3%). The conclusion of this study is found a lot of educational toys for children under five years consisting Pb and the parent’s knowladge is in good level. Suggested to recognize the characteristic of educational toys that consisting Pb. So the kindergarten  teacher and parents must be look after the children when they are playing. Keywords : Pb, Educational toys, Children under five years old, Parent and teacher’s knowladge